2004
DOI: 10.2151/jmsj.2004.1057
|View full text |Cite
|
Sign up to set email alerts
|

Doppler Radar Study on the Successive Development of Snowbands at a Convergence Line near the Coastal Region of Hokuriku District

Abstract: During the field experiment of winter mesoscale convective systems over the Sea of Japan in 2001 (WMO-01), several snowbands associated with a cold front developed remarkably at 10@30 km off the coast of Hokuriku district on 28 and 29 January 2001. Dual-Doppler radar analysis was made to investigate the mechanisms responsible for the successive development of the snowbands.Derived wind fields revealed that a mesoscale convergence line was formed between the prevailing westerly and shallow (@1 km depth), cold s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…1) as well as in that of Niigata. In some case studies, it has been reported that the cold land breeze from the mountains plays a crucial role in the maintenance of snowbands off the coast of Hokuriku (Ishihara et al 1989;Ohigashi and Tsuboki 2005) and off the coast of the area between Niigata and Hokuriku (Yoshihara et al 2004;Eito et al 2005). Ookubo and Kurokawa (2000) suggested that the southwesterly wind deflected by the mountain range in Hokuriku formed a shear line with the northwesterly winter monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…1) as well as in that of Niigata. In some case studies, it has been reported that the cold land breeze from the mountains plays a crucial role in the maintenance of snowbands off the coast of Hokuriku (Ishihara et al 1989;Ohigashi and Tsuboki 2005) and off the coast of the area between Niigata and Hokuriku (Yoshihara et al 2004;Eito et al 2005). Ookubo and Kurokawa (2000) suggested that the southwesterly wind deflected by the mountain range in Hokuriku formed a shear line with the northwesterly winter monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…Intensifications of preexisting precipitation echoes during cold-air outbreaks have also been shown in Tsuboki et al (1989) and Yoshihara et al (2004). The low-level convergence formed along mountain flanks enhances updraft associated with preexisting echoes.…”
Section: Discussion Of Intensification Along the Mountain Flankmentioning
confidence: 54%
“…The unbalanced flow was forced toward the left in the high-pressure region, which formed winds with a southerly component. Ookubo and Kurokawa (2000) and Yoshihara et al (2004) showed that flows deflected by mountains generated heavy snowfall or snowfall intensification during cold-air outbreaks. In their studies, surrounding winds were deflected toward the left in the upwind of mountains and made convergence with the nondeflected flow.…”
Section: Discussion Of Intensification Along the Mountain Flankmentioning
confidence: 99%
See 1 more Smart Citation
“…During the WMO-01, bandshaped snowfall systems were frequently observed around the coastal region of the Hokuriku district. Yoshihara et al (2004) observed several migratory snowbands associated with a cold front on 28 and 29 January, 2001, by using a dual-Doppler radar system. They revealed that a low-level mesoscale convergence line, which formed at 10-30 km offshore, con-tributed significantly to the successive development of the snowbands.…”
Section: Introductionmentioning
confidence: 99%